O desafio de produzir com compromisso social e ambiental: a responsabilidade das empresas - Kich, Jeane (Universidade do Vale do Rio do Sinos, 2009)
Can the corporate environmental responsibility be defined as a mere fashionable business term or as a concept which adds to the existing set of values, rights and obligations to ensure the preservation of life on our planet within a global, integrated and sustainable vision? This issue has permeated the theme addressed in this research, which studied the social and environmental practices of three companies in the city of Canoas, trying to show their real commitment to their context, as a sample of the business vision on the subject. The parameters for the reflection were the different understandings of social responsibility and the main theories of environmental sociology, namely: Risk Society, Beck and Giddens, Sustainable Development, Sachs, and the Ecological Modernization by Buttel, Mol and Spaargaren. Similarly, it sought to understand the reasoning behind the emergence of concepts, revealing the historical facts characterized as corporate environmental accidents that made evident the need for legal reg
Keywords: responsabilidade ambiental; responsabilidade socioambiental; riscos; sustentabilidade; responsabilidade social; environmental responsibility; risk; sustainability; social responsibility; Ciências Sociais Aplicadas